Fungsi, Kategori, dan Peran Sintaksis Bahasa Indonesia dalam Kalimat Efektif Teks Cerita Anak yang Berjudul “Berbeda Itu Tak Apa” pada Buku Ajar Bahasa Indonesia Kelas Satu Sekolah Dasar Kurikulum Merdeka - Nurul Lisa Kusumaningrum; Erina Hidayah; Vivin Widya Sari; Salma Dian Rhamadhan; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Children's story text is an event based on the time sequence experienced or in the form of imagination that tells the world of children. This story text can improve the process of language skills in children by reading. The children's story text entitled